Redesain Tata Lansekap di Area Candi Kidal, Kabupaten Malang, Jawa Timur - Andini, Ni Putu Ayu Mesa; Suryada, I Gusti Agung Bagus; Titisari, Ema Yunita; Paramadhyaksa, I Nyoman Widya (Jurnal Arsitektur Universitas Udayana; Vol 13 No 01 (2025): Jurnal Arsitektur, Universitas Udayana, 2025)
Candi Kidal, an archaeological site located in Desa Rejokidal, Tumpang, Malang Regency, East Java, built around 1248 AD, is a cultural heritage of the Singasari Kingdom with significant historical and cultural value. However, Candi Kidal faces ecological challenges that threaten its historical, cultural, and tourism value. One of the primary issues identified is air pollution caused by unpleasant odors from poultry farming facilities near the temple. This air pollution negatively impacts air quality, while also reducing the attractiveness of Candi Kidal as a tourist destination. Consequently, this could lead to a decrease in tourist visits, harming the site's economic and cultural value. This study examines the potential of redesigning the landscape, particularly through vegetation management, as a solution to address the ecological problems surrounding Candi Kidal. The aim of this research is to analyze the impact of unpleasant odors on visitor comfort and to identify vegetation management strategies that can be implemented to mitigate this issue. With a holistic scientific approach, this research seeks to provide effective solutions for improving the landscape of Candi Kidal, while also contributing to the sustainable preservation and development of this archaeological site. The final results present several innovative landscape design concepts for the Candi Kidal area, such as the strategic arrangement of vegetation and other aesthetic elements, which are shown to significantly reduce odor intensity, improve air quality, enhance the site's aesthetic appeal, and increase visitor comfort. Keywords: Singasari temple, outdoor space arrangement, landscape, vegetation